Hemodialysis in the Treatment of Acute Renal Failure in Tropical Africa: A 20- Year Review at the Korle Bu Teaching Hospital, Accra - Mate-Kole, M. 0.; Yeboah, E. D.; Affram, R. K.; et al. (Taylor & Francis, 2015)
From 1972 to 1992,170 patients with acute renal failure (87 M, 83 F; mean age 32.51 k SE 0.945) underwent hemodialysis at the renal unit of the Korle Bu Teaching Hospital, Accra. Vascular access was established initially by arteriovenous shunt (133 cases), femoral venous cannulation (10 cases), and subclavian vein cannulation (27 cases). The overall mortality for acute renal failure (ARF) was 31.8% (54/170). The mortality for obstetric cases was 43.7% (14/32); for surgical cases, 33.3% (6/18); medical cases, 28.3% (13/32); and gynecologic (posthysterectomy) cases, 28.3% (21). The most important causes of death in ARF were pulmonary edema (42%), sepsis (20%0), and cardiac tamponade (10.4%). Hemodialysis is now established as a form of treatment for ARF and a overall survival rate of 68.2% justifies the development of our program. With improvement of economies of developing countries and health insurance schemes, this form of treatment should be available in all developing countries.
Research Article
Keywords: Hemodialysis; Acute Renal Failure